Adaptive linear neural network approach for three-phase four-wire active power filtering under non-ideal grid and unbalanced load scenarios - Hoon, Yap; Mohd Radzi, Mohd Amran; Al-Ogaili, Ali Saadon (MDPI, 2019)
This paper presents the enhancements performed on the adaptive linear neuron (ADALINE) technique so that it can be applied for active power filtering purposes in a three-phase four-wire system. In the context of active power filtering, the ADALINE technique which was initially developed for a single-phase two-wire system has been further expanded to suit three-phase three-wire system. For both systems, ADALINE techniques have been reported to be effective even when the grid voltage is distorted and/or unbalanced. However, further works that study the possibility to apply ADALINE technique in a three-phase four-wire system which invariably carries unbalanced loads, are rather limited. Hence, in this work, a control algorithm (named as enhanced-ADALINE) which combines the strength of highly selective filter (HSF), ADALINE concept and averaging function is proposed, to manage harmonics mitigation by shunt active power filter (SAPF) under non-ideal grid and unbalanced load scenarios. MATLAB-Simulink software is utilized to conduct an exhaustive simulation study which includes circuit connection of SAPF in a three-phase four-wire system, design of control algorithms, and performance assessments. Benchmarking with the existing algorithm is performed to examine the benefits of using the proposed algorithm. From the analysis, simulation findings are presented and thoroughly discussed to verify design concept, capability, and relevance of the proposed algorithm.